2018
DOI: 10.1002/anie.201712019
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of Arylated Furans by a Sequential Rh‐Catalyzed Arylation and Cycloisomerization of Cyclopropenes

Abstract: A novel and efficient strategy for the synthesis of arylated furans was successfully developed by a Rh -catalyzed coupling of N-phenoxyacetamides and cyclopropenyl esters. Mechanistic investigation reveals that the arylated furans are formed via arylation of the cyclopropenyl esters followed by cycloisomerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(31 citation statements)
references
References 91 publications
0
29
0
2
Order By: Relevance
“…To circumvent all these difficulties in 2018, they reported an efficient method for the synthesis of various substituted arylated furans 96 by rhodium-catalyzed coupling of N-phenoxyacetamides 94 with cyclopropenyl esters 95 (Scheme 20). [51] The diazo ketone compounds are used for the synthesis of furans through catalytic cyclopropenation of alkynes with subsequent rearrangement of the cycloprop-2-en-1-yl ketones reported by Garner [52] and Padwa. [52] In 2015, Doyle's group [52] reported that enoldiazoacetates and enoldiazoacetamides undergo dinitrogen extrusion thermally and with selected catalysts, to form donor-acceptor cyclopropenes.…”
Section: Metal Catalyzed Heterocyclic Synthesismentioning
confidence: 99%
“…To circumvent all these difficulties in 2018, they reported an efficient method for the synthesis of various substituted arylated furans 96 by rhodium-catalyzed coupling of N-phenoxyacetamides 94 with cyclopropenyl esters 95 (Scheme 20). [51] The diazo ketone compounds are used for the synthesis of furans through catalytic cyclopropenation of alkynes with subsequent rearrangement of the cycloprop-2-en-1-yl ketones reported by Garner [52] and Padwa. [52] In 2015, Doyle's group [52] reported that enoldiazoacetates and enoldiazoacetamides undergo dinitrogen extrusion thermally and with selected catalysts, to form donor-acceptor cyclopropenes.…”
Section: Metal Catalyzed Heterocyclic Synthesismentioning
confidence: 99%
“…Glorius and co-workers, reported Rh III -catalyzed synthesis of arylated furans by coupling cyclopropenyl esters and N-phenoxyacetamides (Scheme 3). [11] The authors investigated various possible pathways, however,t he arylation of cyclopropene by anti-b-H elimination followed by the subsequent cycloisomersation wasc onsidered to be the favorable one. Them ethodology besides being mild and additive-free, offers further transformation to access benzofuran-3(2H)-one and butenolide derivatives.…”
Section: Three-membered Rings In Càhfunctionalizationmentioning
confidence: 99%
“…As we know, the many synthetic strategies including Paal‐Knorr reaction and Feist‐Benary reaction have been developed, but the construction of privileged five‐membered oxygenated heterocycles is still a challenge. Recently, the transition‐metals have been widely employed to promote the synthesis of substituted furans as catalysts under the mild reaction conditions . For instance, Trost et al disclosed a successful catalytic (3 + 2) cycloaddition involving Pd‐oxyallyl species to yield a diverse range of cis‐fused methylene tetrahydrofurans .…”
Section: Introductionmentioning
confidence: 99%